THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN CRIMINAL PROCEDURE - Monika Porwisz (Probacja, 2025)
The purpose of this paper is to identify areas in which artificial intelligence (AI) can be applied in criminal procedure, with a view to improving the efficiency of proceedings in terms of both time and cost. Addressing the issues raised required a review of international and Polish regulations concerning the definition and conceptual use of AI, as well as a review of the relevant literature. The areas analysed were essential for indicating the directions for the application of AI in criminal procedure and for justifying the need to implement the proposed solutions in line with existing legal standards.